2006
DOI: 10.1111/j.1525-1497.2006.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional integrative medicine intervention to improve cardiovascular risk

Abstract: A multidimensional intervention based on integrative medicine principles reduced risk of CHD, possibly by increasing exercise and improving weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(126 citation statements)
references
References 34 publications
4
121
0
1
Order By: Relevance
“…Our findings are consistent with those of Edelman et al, 6 who documented increased days of exercise and greater weight loss among those who participated in PHP-IHC compared to those receiving usual care. Likewise, Wolever, et al 8 demonstrated increased patient activation, social support, and exercise frequency among patients with type II diabetes who received PHP-IHC compared to those receiving usual care.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings are consistent with those of Edelman et al, 6 who documented increased days of exercise and greater weight loss among those who participated in PHP-IHC compared to those receiving usual care. Likewise, Wolever, et al 8 demonstrated increased patient activation, social support, and exercise frequency among patients with type II diabetes who received PHP-IHC compared to those receiving usual care.…”
Section: Discussionsupporting
confidence: 83%
“…For example, although only emerging in the past decade, one brand of integrative health coaching has been well described, standardized within a framework that allows for individual tailoring, 87,88 and shown to be effective. 17,21,93,94 Perhaps the best example of standardization of individually tailored processes is seen in motivational interviewing; the MI processes have been well described, standardized within a framework, widely disseminated, and demonstrated to be effective in many settings. 9,78,79,90,[95][96][97] Moreover, motivational interviewing has the advantage of several psychometrically sound program evaluation measures (eg, Motivational Interviewing Skills Code, 98 Motivational Interviewing Treatment Integrity 99 ) that can be used to ensure intervention integrity and assess intervention outcomes for common threats to validity.…”
Section: Individualized Vs Protocol-driven Coachingmentioning
confidence: 99%
“…Other CVD primary prevention studies achieved larger effects but required greater resources, and many included multiple contacts with clinicians. 8,10,11,[21][22][23][24] If a measurable positive effect of a more limited intervention like ours can be accomplished at a sufficiently low cost, it may be a worthwhile approach to adopt. If the process of delivering these messages can be fully automated (such as using a patient portal connected to the electronic health record), this may reduce the cost of providing this service further.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies with repeated exposure to risk messages and counseling have shown the most favorable results. 8,10,11,22,23 An additional study is needed to examine whether repeated delivery increases efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation